2007
DOI: 10.1258/135763307780908058
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the benefits of home telecare for frail elderly people and those with long-term conditions

Abstract: We have conducted a systematic review of home telecare for frail elderly people and for patients with chronic conditions. We searched 17 electronic databases, the reference lists of identified studies, conference proceedings and Websites for studies available in January 2006. We identified summaries of 8666 studies, which were assessed independently for relevance by two reviewers. Randomized controlled trials of any size and observational studies with 80 or more participants were eligible for inclusion if they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
231
0
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 321 publications
(245 citation statements)
references
References 9 publications
(20 reference statements)
4
231
0
10
Order By: Relevance
“…While trials of telecare services suggest substantial benefits at the individual level, the understanding of the effect of the introduction of telecare on the care system as a whole is unclear. Telecare has generally been evaluated with a view to exploring clinical outcomes or proving the technology, rather than its systemic impacts (Barlow et al, 2007). Available data from pilot or trial telecare schemes in specific settings and with specific (and sometimes only vaguely defined) patient groups are unlikely to give more than an indication of the potential effects of telecare in other settings and even less so its systemic implications.…”
Section: Background: Telecarementioning
confidence: 99%
See 1 more Smart Citation
“…While trials of telecare services suggest substantial benefits at the individual level, the understanding of the effect of the introduction of telecare on the care system as a whole is unclear. Telecare has generally been evaluated with a view to exploring clinical outcomes or proving the technology, rather than its systemic impacts (Barlow et al, 2007). Available data from pilot or trial telecare schemes in specific settings and with specific (and sometimes only vaguely defined) patient groups are unlikely to give more than an indication of the potential effects of telecare in other settings and even less so its systemic implications.…”
Section: Background: Telecarementioning
confidence: 99%
“…In particular, large longitudinal studies of the changes in health status and functional ability of people in the community are lacking. (Barlow et al, 2007).…”
Section: Background: Telecarementioning
confidence: 99%
“…With respect to the related works, author acknowledges the approach using a systematic literature review conducted by Gaikwad and Warren (2009) which evaluated the feasibility and benefits of home-based ICT enabled interventions for chronic disease management. Using similar approach, Barlow et al (2007) conducted a literature review of home tele-care related to the frail elderly and chronically ill. The study of Barlow et al (2007) reported about the effective Tele-care interventions to reducing health service use and improving clinical indicators and reducing health service use.…”
Section: Discussionmentioning
confidence: 99%
“…Using similar approach, Barlow et al (2007) conducted a literature review of home tele-care related to the frail elderly and chronically ill. The study of Barlow et al (2007) reported about the effective Tele-care interventions to reducing health service use and improving clinical indicators and reducing health service use. However, a particular shortfall of the current study is a cost-benefit analysis related to specific technological implementations which could add value to its further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…5 Telehealth has been shown to improve health outcomes [8][9][10][11] and reduce health service use in specialities such as chronic heart failure, respiratory conditions and diabetes management. 8,9,12,13 In chronic heart failure, there is evidence that telemonitoring not only reduces hospital admissions, but may also be effective for disease management in high-risk patients. 10 Other studies have shown that telemonitoring is associated with lower rates of mortality for patients.…”
mentioning
confidence: 99%